Seeding growth approach to gold nanoparticles with diameters ranging from 10 to 80 nanometers in organic solvent - Stanglmair, Christoph; Scheeler, Sebastian Paul; Pacholski, Claudia (European journal of inorganic chemistry, 2014)
Abstract To accommodate the high demand for gold nanoparticles, which is generated by the extraordinary optical properties of plasmonic metamaterials, a focus has been placed on their large-scale synthesis for several years. In this work, a simple method for the preparation of nearly monodisperse gold nanoparticles with diameters of up to 80 nm is presented. For this purpose, gold nanoparticles with an average diameter of 9 nm were synthesized in toluene by using oleylamine both as a reducing and stabilizing agent. These gold nanoparticles act as seeds for a subsequent growth reaction in which the same precursors are slowly added to the reaction vessel. During the reaction, the gold nanoparticles start to agglomerate when they reach a certain size (ca. 20 nm). Despite their agglomeration, they can be grown further without impairing their size distribution or morphology. The gold nanoparticle agglomerates can be separated by stabilization with thiol-terminated polystyrene.